Kompoziti, izdelani s sintezo dvofaznih (S+L) mešanic - Anžel, Ivan (Kovine zlitine tehnologije, 1998)
Metal matrix composites (MMCs) consist of metal matrix and reinforcing phase, which can take one of several morphologies including continuous or discontinuous fibre, whiskers, or particulates. To date, many different technologies of production the MMCs have been developed. Especially attractive becomes in-situ composite technology which solves the problem of wettability of the reinforcing particulates by the matrix. On the other hand a problem of the reinforcing phase fraction variation in the composite arises at this technology. In this paper we present the model of a new processing route, which can be used for the fabraication of paarticulate reinforced metal matrix composites and which solves both, the problem of wettability and the problem of the reinforcing phase fraction variation in the composite.
Keywords: kompoziti; zlitine; aluminij; aluminum; silicij; fazni prehodi; večfazni sistemi